2010
DOI: 10.1016/j.otohns.2010.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and efficacy of head and neck cancer screening

Abstract: Objectives This study was designed to (1) describe the demographics and (2) determine the efficacy of a head and neck cancer screening program in order to optimize future programs. Methods After IRB approval, we conducted a retrospective cohort study to review a single institution’s 14-year experience (1996–2009) conducting a free annual head and neck cancer screening clinic. Available demographic and clinical data, as well as clinical outcomes were analyzed for all participants (n=761). The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 26 publications
1
52
0
1
Order By: Relevance
“…18 However, another study found that those who evidenced abnormal findings were significantly older and smoked more packs of cigarettes per day than those participants who did not evidence abnormal findings. 19 As all our participants were covered by national health insurance, the difference between those with insurance and those without could not be investigated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…18 However, another study found that those who evidenced abnormal findings were significantly older and smoked more packs of cigarettes per day than those participants who did not evidence abnormal findings. 19 As all our participants were covered by national health insurance, the difference between those with insurance and those without could not be investigated.…”
Section: Discussionmentioning
confidence: 96%
“…18 Only 0.9% of participants had malignant or premalignant lesions confirmed. The authors suggested that such screening programs should target patients with identifiable risk factors.…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we chose a homogenous population of patients with oral cavity squamous cell carcinoma. This patient population is associated with risk factors such as smoking that in and of themselves may predispose patients to impaired healing and subsequent plate complications [28]. Other non-surgical factors such as diabetes has been shown to significantly predict plate complications [9].…”
Section: Discussionmentioning
confidence: 99%
“…29 In the present study, a high prevalence of white skin individuals (90.04%) was observed, similar to the findings from a study conducted recently in the southern states of Brazil 30 and the Midwest of the United States. 31 However, Hayat et al 32 observed a higher prevalence of head and neck cancer among AfricanAmerican descendants from different areas of the United States.…”
mentioning
confidence: 99%